Plan de desarrollo y ordenamiento territorial (PDOT) de la parroquia Vilcabamba perteneciente al cantón Loja. - Armijos Espinoza, Nixon Víctor (2012)
The Vestry of Vilcabamba, in order to continue contributing to the development of its inhabitants, has proposed to undertake certain actions that enable it to perform more efficiently with the responsibilities to their constituents and also assist in the consolidation the spaces created during the planning consultation parish and county. This document is developed in three parts: a diagnosis for each system: ecological, economic, human settlement, mobility and connectivity, socio cultural and land management. The second part contains the recommendations and proposals from the different seminars and workshops in the socialization of the Plan, then there is the vision that has the population of both the desired society, as the land of the parish. Finally, establishing lines of action with the respective programs and projects that contribute to the development and management of the parish. In the stage of diagnosis was a description of the most important and relevant aspects of each system, the same that underlie the development plan, allowing us to have a clear idea of the strengths and weaknesses that owns the territory of the parish. With a clear vision of what is in the territory proceeded to plan the new territorial model to be achieved for the parish, this proposal I perform in a participatory manner, where the inhabitants of the parish were the decided that was the right way that suits their territorial conditions. This proposal would be a simple statement, but it makes the management plan that is generated by the projects, which will steer the country towards the new territorial model, so this plan was developed a number of projects defined by lines action and these in turn respond to goals set for each of the territorial systems.